“Als je je maar jong voelt!” “Oud maar nog jong van hart!” - Marcoen, Alfons (Tijdschrift voor Gerontologie en Geriatrie, 2012)
Bespreking: Weiss,D.,& Lang, F. R. (2012). “They” are old but “I” feel younger: Age-group dissociation as a self-protective strategy in old age. Psychology and Aging, 27, 153-163. Weiss,D.,& Freund, A. (2012). Still young at heart: Negative age-related information motivates distancing from same-aged people. Psychology and Aging, 27, 173- 180.